Legal Review of the Notary's Authority in Issuing Inheritance Rights Statements for All Classes: A Study of the Inheritance Law Diversity in Indonesia - Dewi, Reza Liasta (Riwayat: Educational Journal of History and Humanities, 2025)
The diversity of inheritance law systems in Indonesia has created challenges in ensuring legal certainty for heirs. This article analyzes the authority of notaries in drafting authentic Certificates of InheritanceorKeteranganHak Waris(KHW) applicable to all demographic groups in Indonesia. The study employs a normative juridical method with a statutory approach. The findings reveal that notaries possess exclusive authority in creating authentic deeds related to KHW, which are crucial for guaranteeing legal certainty and the validity of legal evidence in inheritance matters. This article recommends legal harmonization to eliminate discrimination in the implementation of inheritance law.